1994
DOI: 10.1002/cyto.990160407
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of the cell cycle in polyamine‐depleted cells

Abstract: Polyamines are found in all cells but their function is not fully understood. We have studied the effect of polyamines on the passage of cells through the cell cycle using a polyamine auxotrophic mutant, CHO-P22, which has no detectable ornithine decarboxylase activity. The ability of these cells to grow without serum al-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…These data fit with observations that polyamines are necessary for the G1\S transition [34a,35] or the progression through S phase [36,37]. Decreased polyamine concentrations would then be expected to decrease mitoses, as seen here and in other systems [36,38]. Down-regulation of cellular polyamines appears to be necessary not only for cell growth but also for survival.…”
Section: Discussionsupporting
confidence: 86%
“…These data fit with observations that polyamines are necessary for the G1\S transition [34a,35] or the progression through S phase [36,37]. Decreased polyamine concentrations would then be expected to decrease mitoses, as seen here and in other systems [36,38]. Down-regulation of cellular polyamines appears to be necessary not only for cell growth but also for survival.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, CHENSpm treatment produces a significant G 2 ͞M block concurrent with its cytotoxic activity. This effect by CHENSpm is somewhat unusual in that interference with polyamines metabolism and polyamine depletion generally produce a G 1 ͞S block if they have any measurable effect on the cell cycle at all (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…This early effect has been possible to detect due to the sensitivity of the flow cytometry method used with BrdUrd. Earlier reports have dealt with impaired DNA replication after several days of inhibitor treatment (Anehus et al, 1984;Westin et al, 1991 ;Pohjanpelto et al, 1994). Pohjanpelto and Hiiltta (1996) have shown that polyamine depletion reversibly blocks synthesis of high-molecutar-mass DNA and leads to accumulation of short DNA pieces, suggesting a role for polyamines in joining the Okazaki fragments.…”
Section: Discussionmentioning
confidence: 99%